Keterampilan Menulis Teks Anekdot dengan Tema Pendidikan Siswa Kelas X B1 SMA Negeri 06 Kota Bengkulu - Saputra, Ervan Andeka; Utomo, Padi; Wardhana, Dian Eka Candra (UNIB Press, 2025)
This study aims to describe the students’ skill in writing anecdote texts with educational themes among tenth-grade students (Class X B1) of SMA Negeri 06 Bengkulu City. The research employed a quantitative method. The population consisted of all 34 students of Class X B1, and the sample included the same number of students. The data were collected through a writing test and analyzed using the mean score formula. The results showed that the students’ skill in writing anecdote texts with educational themes was categorized as poor, with an average score of 50.00. Based on three assessed aspects, the results were as follows: (1) text structure obtained an average score of 18.08 (fair category); (2) content relevance to the theme reached an average score of 13.08 (fair category); and (3) linguistic accuracy based on the Indonesian Spelling System (EYD) obtained an average score of 14.63 (fair category).